Adoptive T‐cell immunotherapy for ganciclovir‐resistant CMV disease after lung transplantation. Issue 3 (27th March 2015) - Holmes‐Liew, Chien‐Li; Holmes, Mark; Beagley, Leone; Hopkins, Peter; Chambers, Daniel; Smith, Corey; Khanna, Rajiv
Abstract : Infections with cytomegalovirus (CMV) can induce severe complications after solid organ transplantation (SOT). The prognosis for ganciclovir‐resistant CMV infection and disease is particularly poor. Whereas adoptive transfer of CMV‐specific T cells has emerged as a powerful tool in hematopoietic stem cell transplant patients, its translation into the SOT setting remains a significant challenge as underlying immunosuppression inhibits the virus‐specific T‐cell response in vivo . Here, we demonstrate successful expansion and adoptive transfer of autologous CMV‐specific T cells from a seronegative recipient of a seropositive lung allograft with ganciclovir‐resistant CMV disease, resulting in the long‐term reconstitution of protective anti‐viral immunity, CMV infection, disease‐free survival and no allograft rejection.